Water-containing rubber composition and method for producing rubber molded article

A water-containing rubber composition with aramid nanofibers addresses adhesion and dispersibility challenges, enhancing the elastic modulus and abrasion resistance of rubber products by ensuring uniform distribution and bonding.

JP7609710B2Active Publication Date: 2025-01-07TEIJIN LTD
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
JP2021092347
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-06-01
Publication Date
2025-01-07
Estimated Expiration
2041-06-01

AI Technical Summary

Technical Problem

Existing methods for reinforcing rubber with aramid short fibers face challenges such as low adhesion, poor dispersibility, and agglomeration, leading to inadequate wear resistance and mechanical properties.

Method used

A water-containing rubber composition comprising aramid nanofibers with an average diameter of less than 500 nm, a specific weight ratio of aramid nanofibers to rubber, and controlled moisture content, which is used as a masterbatch to improve adhesion and dispersibility, enhancing rubber elastic modulus and abrasion resistance.

Benefits of technology

The composition effectively improves the elastic modulus and abrasion resistance of rubber products by ensuring uniform distribution and bonding of aramid nanofibers, overcoming agglomeration issues.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007609710000001
    Figure 0007609710000001
Patent Text Reader

Abstract

To provide a moisture-containing rubber composition which is used as a state of a master batch in rubber production, and gives high rubber elasticity, and abrasion resistance to an obtained rubber.SOLUTION: A moisture-containing rubber composition includes: an aramid nanofiber; a rubber; and water, where the aramid nanofiber has an average fiber diameter of less than 500 nm, the weight ratio of the aramid nanofiber, and the rubber in the moisture-containing rubber composition is 1:99-35:65, and the weight ratio of a total of the aramid nanofiber and the rubber, and water is 98:2-1:99. The moisture-containing rubber composition is used as a master batch material for production of a rubber composition.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a moisture-containing rubber composition, and more particularly to a moisture-containing rubber composition that is used as a raw material in the production of a fiber-reinforced rubber molded article, particularly in the form of a masterbatch, and a method for producing a rubber molded article using the same. [Background technology]

[0002] Conventionally, in order to improve the mechanical properties of rubber molded articles, it has been considered to reinforce them by blending short fibers such as cellulose fibers, nylon fibers, polyester fibers, aramid fibers, etc. Among these, short fibers of aramid fibers are widely used because of their excellent mechanical properties, fatigue resistance, heat resistance, and chemical properties.

[0003] However, since the surface of aramid short fibers is relatively inactive, they have low adhesive strength with rubber and poor dispersibility when mixed into rubber, so that the inherent excellent properties of aramid short fibers cannot be fully exhibited. Even if aramid short fibers are added to rubber, they are not completely uniformly distributed during use, so that wear progresses from the parts where no aramid short fibers are present, and sufficient wear resistance cannot be obtained.

[0004] As a means for improving the adhesive strength between the short reinforcing fibers and the rubber, it is possible to increase the contact area between the short reinforcing fibers and the rubber by reducing the fiber diameter of the short reinforcing fibers or by using pulp with fibril on the surface of the short reinforcing fibers. However, the larger the contact area, the more difficult it becomes to uniformly distribute the reinforcing fibers in the rubber.

[0005] Among these, Patent Document 1 proposes a granular elastomer composition for use as a masterbatch material in which aramid pulp having fibrils on the fiber surface is mixed in advance with a liquid elastomer. Although the fibril portion of aramid pulp is fine, the stem portion is thick and the fibrils may be cut off from the stem, so the adhesive strength with rubber is still insufficient, and further improvement in rubber reinforcement properties is expected.

[0006] Recently, a technique for nano-sizing aramid fibers has been proposed. For example, Non-Patent Document 1 and Non-Patent Document 2 propose a method for obtaining nano-sized aramid fibers, i.e., aramid nanofibers, by treating aramid fibers in a dimethyl sulfoxide solvent containing potassium hydroxide, or by spraying alkali-treated aramid fibers with high-pressure water. By using these aramid nanofibers to reinforce rubber, it is expected that the adhesive strength with the rubber will be improved, and the rubber elastic modulus and abrasion resistance will be greatly improved.

[0007] Patent Document 2 proposes a method for producing a short fiber-containing rubber masterbatch, in which an aqueous dispersion of cellulose or aramid short fibers with an average fiber diameter of less than 0.5 μm (500 nm) is mixed with rubber latex by stirring, and the mixture is sprayed and dried under an atmosphere of shock waves generated by pulse combustion. However, since aramid fibers exhibit very strong hydrogen bonds, even after mixing with rubber latex, if the moisture is completely removed, the aramid nanofibers that are partially in contact with each other will aggregate in the masterbatch. Then, once the aramid nanofibers aggregate, it becomes difficult to redisperse them in the subsequent process, making it difficult to obtain a good reinforcing effect.

[0008] Non-Patent Documents 3 and 4 propose a method of adding epichlorohydrin to a potassium hydroxide-added dimethyl sulfoxide solvent containing aramid nanofibers, obtaining an aqueous dispersion of aramid nanofibers modified with epichlorohydrin, mixing the aqueous dispersion with a latex (aqueous dispersion) mixture of carboxylated nitrile rubber and styrene butadiene rubber or a latex of styrene butadiene rubber alone, removing water, and adding a vulcanizing agent to obtain a rubber composition. In this method, the surface of the aramid nanofibers is modified with epichlorohydrin, which makes it easier to prevent the aramid nanofibers from aggregating together, but the process of performing epichlorohydrin treatment in a solvent requires a long treatment time and epichlorohydrin remaining in the solvent makes it difficult to recover a high-purity solvent, so there remain industrial challenges. [Prior art documents] [Patent documents]

[0009] [Patent Document 1] Japanese Patent Publication No. 137940 / 1983 [Patent Document 2] Patent No. 3998692 [Non-patent literature]

[0010] [Non-Patent Document 1] ACS Nano 2011, 5, 6945. [Non-Patent Document 2] RSC Adv. 2014, 4, 40377. [Non-Patent Document 3] Composites Part B: Engineering 2019,166,196-203 [Non-Patent Document 4] Materials Chemistry and Physics 2019,238,121926 Summary of the Invention [Problem to be solved by the invention]

[0011] An object of the present invention is to provide a water-containing rubber composition which can be used in the form of a masterbatch in the production of rubber and which can impart high rubber elasticity and abrasion resistance to the resulting rubber. [Means for solving the problem]

[0012] That is, the present invention relates to a moisture-containing rubber composition comprising aramid nanofibers, rubber and water, wherein the aramid nanofibers have an average fiber diameter of less than 500 nm, the weight ratio of the aramid nanofibers to the rubber in the moisture-containing rubber composition is 1:99 to 35:65, and the weight ratio of the sum of the aramid nanofibers and the rubber to the water is 98:2 to 1:99, and the moisture-containing rubber composition is used as a master batch material for producing a rubber composition. Effect of the Invention

[0013] According to the present invention, there can be provided a water-containing rubber composition which is used in the form of a masterbatch in the production of rubber and which can impart high rubber elasticity and abrasion resistance to the resulting rubber. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0014] The present invention will be described in detail below.

[0015] [Aramid nanofiber] In the present invention, the aramid nanofibers are aromatic polyamide fibers having an average fiber diameter of 500 nm or less.

[0016] Specific examples of aromatic polyamide fibers include polyparaphenylene terephthalamide fibers, which are para-type aromatic polyamide fibers (e.g., Twaron (registered trademark) manufactured by Teijin Aramid BV), copolyparaphenylene-3,4'-oxydiphenylene-terephthalamide fibers, which are copolymer-type aromatic polyamide fibers (e.g., Technora (registered trademark) manufactured by Teijin Limited), and polymetaphenylene isophthalamide fibers, which are meta-type aromatic polyamide fibers (e.g., Conex (registered trademark) manufactured by Teijin Limited).

[0017] As the aramid nanofiber, among aromatic polyamide fibers, para-aromatic polyamide fibers having high strength and elastic modulus are preferable. The aramid nanofibers can be produced by a known method using the aromatic polyamide fibers described above, for example, a method of stirring and treating the aromatic polyamide fibers in a polar solvent such as dimethyl sulfoxide containing a strong base such as potassium hydroxide, a method of treating the aromatic polyamide fibers under high shear force such as by spraying high-pressure water, or a method of treating the aromatic polyamide fibers by electrospinning.

[0018] Among these, a method in which aromatic polyamide fibers are stirred in a polar solvent such as dimethyl sulfoxide containing a strong base such as potassium hydroxide is preferred because it produces aramid nanofibers with relatively little variation in fiber diameter.

[0019] The average fiber diameter of the aramid nanofiber is 500 nm or less, preferably 100 nm or less. If the average fiber diameter exceeds 500 nm, it is difficult to realize the high specific surface area that is a characteristic of nanofibers, and sufficient adhesive strength with rubber cannot be obtained, and there are many areas where the aramid nanofibers do not exist, so that the elastic modulus and abrasion resistance of the rubber cannot be sufficiently improved, which is not preferable. The lower limit of the average fiber diameter is, for example, 1 nm. This is because it is difficult to manufacture fibers with an average fiber diameter of less than 1 nm.

[0020] The aspect ratio of the aramid nanofiber, expressed by fiber length / fiber diameter, is preferably 10 to 10,000, more preferably 50 to 5,000. If the aspect ratio is less than 10, sufficient reinforcement properties cannot be obtained, which is undesirable. This is presumably because each individual aramid nanofiber is likely to come out of the rubber. On the other hand, if the aspect ratio exceeds 10,000, entanglement between the aramid nanofibers is likely to occur, making it difficult to obtain uniform dispersion, which is undesirable.

[0021] [Rubber] The rubber contained in the water-containing rubber composition of the present invention is a polymeric material having elasticity. As the rubber, unvulcanized or uncrosslinked rubber is used, and preferably, natural rubber (NR), styrene butadiene rubber (SBR), nitrile rubber (NBR), polyisoprene rubber (IR), butadiene rubber (BR), butyl rubber (IIR), ethylene propylene rubber (EPM), chloroprene rubber (CR), acrylic rubber (ACM), silicone rubber (Q), and fluororubber (FKM) are used before vulcanization. A plurality of types of rubber may be included. Styrene butadiene rubber is particularly preferred as the rubber.

[0022] [Ratio of aramid nanofiber to rubber component] In the water-containing rubber composition of the present invention, the weight ratio of aramid nanofiber to rubber is 1:99 to 35:65. If the amount of aramid nanofiber is less than 1% by weight, sufficient reinforcement properties cannot be obtained. On the other hand, if the amount of aramid nanofiber is more than 35% by weight, the amount of rubber between the single fibers of the aramid nanofiber is insufficient, the distance between the aramid nanofibers is shortened, and aggregation due to hydrogen bonds or a large amount of entanglement occurs, which is not preferable.

[0023] [Moisture content in water-containing rubber composition] In the water-containing rubber composition of the present invention, the weight ratio of the total of the aramid nanofibers and the rubber to the water is 98:2 to 1:99, preferably 50:50 to 1:99. When water is present in the rubber composition within this weight ratio range, water is present between one aramid nanofiber and another aramid nanofiber, and it is possible to suppress the aramid nanofibers from re-aggregating due to hydrogen bonding. On the other hand, if the weight ratio of the total of the aramid nanofibers and the rubber to the water exceeds 1:99 and the water-containing rubber composition contains a large amount of water, most of the water will be water, which will increase the industrial logistics cost and make it difficult to remove the water during use.

[0024] The water-containing rubber composition of the present invention may further contain additives that are generally used in general rubbers, such as reinforcing agents (fillers) such as carbon black and silica, various oils, antioxidants, plasticizers, etc. These additives can be used by kneading them in a general manner.

[0025] [Method for producing water-containing rubber composition] The water-containing rubber composition of the present invention can be produced by mixing an aramid nanofiber water dispersion and a rubber water dispersion in a solids weight ratio of aramid nanofiber to rubber of 1:99 to 35:65 to obtain a rubber mixture, and then removing a portion of the water.

[0026] The aramid nanofiber water dispersion can be produced by adding water stepwise to an organic solvent in which aramid nanofibers are dissolved or dispersed, thereby replacing the organic solvent with water. The rubber water dispersion can be produced by adding water stepwise to an organic solvent in which rubber is dissolved or dispersed, thereby replacing the organic solvent with water. A rubber water dispersion commercially available as a rubber latex can also be used.

[0027] [Master batch] The water-containing rubber composition of the present invention is used for producing a rubber molded article, and is compounded in the form of a masterbatch.

[0028] The amount of aramid nanofibers contained in the rubber molded body by using the water-containing rubber composition of the present invention in the form of a master batch is preferably 0.1 to 30% by weight, more preferably 0.5 to 20% by weight, based on the total weight of the rubber in the rubber molded body. When the rubber molded body contains aramid nanofibers in this range, the elastic modulus and abrasion resistance of the finally obtained rubber molded body can be improved. If the content is less than 0.1% by weight, the reinforcing effect of the aramid nanofibers cannot be sufficiently obtained, which is not preferable. On the other hand, if the content exceeds 30% by weight, it becomes difficult to uniformly disperse the aramid nanofibers, and the reinforcing effect commensurate with the amount added cannot be obtained, which is not preferable.

[0029] [Method for producing rubber molded body] The present invention further provides a method for producing a rubber molded body, comprising: a first step of mixing an aramid nanofiber water dispersion and a rubber water dispersion in a solids weight ratio of aramid nanofiber to rubber of 1:99 to 35:65, and further removing a part of the water to obtain a water-containing rubber composition; a second step of mixing the water-containing rubber composition obtained in the first step with solid rubber, and further removing the water to obtain a solid rubber composition; a third step of mixing the solid rubber composition obtained in the second step with a vulcanizing agent and / or a crosslinking agent to obtain an unvulcanized rubber composition and / or an uncrosslinked rubber composition; and a fourth step of vulcanizing and / or crosslinking the unvulcanized and / or uncrosslinked rubber composition obtained in the third step to obtain a rubber molded body.

[0030] The first step is a step of mixing an aramid nanofiber water dispersion and a rubber water dispersion in a solids weight ratio of aramid nanofiber to rubber of 1:99 to 35:65, and then removing a part of the water to obtain a water-containing rubber composition. By removing a part of the water, the weight ratio of the total of the aramid nanofiber and rubber to water in the obtained water-containing rubber composition is set to 98:2 to 1:99.

[0031] The rubber contained in the rubber water dispersion is a polymeric material having elasticity. As the rubber, unvulcanized or uncrosslinked rubber is used, and preferably, natural rubber (NR), styrene butadiene rubber (SBR), nitrile rubber (NBR), polyisoprene rubber (IR), butadiene rubber (BR), butyl rubber (IIR), ethylene propylene rubber (EPM), chloroprene rubber (CR), acrylic rubber (ACM), silicone rubber (Q), and fluororubber (FKM) are used before vulcanization. A plurality of types of rubber may be included. Styrene butadiene rubber is particularly preferred as the rubber.

[0032] The second step is a step of mixing the water-containing rubber composition obtained in the first step with solid rubber, and then removing the water to obtain a solid rubber composition. The solid rubber used here is pre-vulcanized or pre-crosslinked, and pre-vulcanized natural rubber (NR), styrene butadiene rubber (SBR), nitrile rubber (NBR), polyisoprene rubber (IR), butadiene rubber (BR), butyl rubber (IIR), ethylene propylene rubber (EPM), chloroprene rubber (CR), acrylic rubber (ACM), silicone rubber (Q), and fluororubber (FKM) can be used. Multiple types of solid rubber may be used.

[0033] It is preferable that this solid rubber has a high affinity to the rubber contained in the water-containing rubber composition of the present invention. Therefore, it is preferable that the solid rubber shows a Hansen solubility parameter close to that of the rubber of the water-containing rubber composition of the present invention. Here, "close" means that the difference in Hansen solubility parameter is 2 or less, preferably 1 or less.

[0034] The water-containing rubber composition and the solid rubber can be mixed using a kneading machine such as a pressure kneader or a Banbury mixer, which are generally used for kneading rubber. In these kneading machines, the kneading temperature is set to 100° C. or higher and lower than 180° C., and water is removed during kneading to obtain a solid rubber composition.

[0035] The third step is a step of mixing the solid rubber composition obtained in the second step with a vulcanizing agent and / or a crosslinking agent to obtain an unvulcanized and / or uncrosslinked rubber composition. This mixing is preferably performed in a state where the water-containing rubber composition is cooled to a temperature at which vulcanization and / or crosslinking does not proceed.

[0036] The fourth step is a step of vulcanizing and / or crosslinking the unvulcanized and / or uncrosslinked rubber composition obtained in the third step to form a rubber molded article. EXAMPLES

[0037] The present invention will be described in more detail below with reference to examples. The evaluation methods used in the examples are as follows.

[0038] (1) Average fiber diameter The rubber component of the unvulcanized and / or uncrosslinked rubber composition was dissolved in toluene to obtain a toluene solution containing aramid nanofibers. The toluene solution was spread thinly with a glass rod and dried in a dryer at 70°C to obtain a sheet-like sample made of aramid nanofibers.

[0039] The structure of the samples was observed using a scanning electron microscope (manufactured by JEOL Ltd., model number: JSM-6330F). From the image observed at a magnification setting of 50,000 times, an image region of 1,800 nm to 2,000 nm horizontally and 1,200 nm to 1,500 nm vertically was selected, and the image region was further divided vertically into 4 and horizontally into 4 to define a total of 16 grid regions. One sample present in each grid region was selected, and the fiber diameter was measured on the image. The fiber diameters of a total of 16 samples were measured, and the average value of these was taken as the average fiber diameter.

[0040] (2) Stress at 5% elongation and 10% elongation of vulcanized rubber sheet For the vulcanized rubber sheet, samples were cut in the orientation direction of the aramid nanofibers, and tensile tests were carried out using the JIS K6251 dumbbell No. 3 method to measure the stress at 5% elongation and 10% elongation. The higher these stresses, the better the elastic modulus.

[0041] (3) Abrasion resistance of vulcanized rubber sheets The surface of the vulcanized rubber sheet was rubbed with sandpaper no. 320 to evaluate its abrasion resistance. Specifically, using an abrasion and wear tester manufactured by Orientec Co., Ltd., the sheet was rotated and abraded at a speed of 100 rpm under a load of 0.19 MPa against a metal plate with sandpaper no. 320 attached, so that the cross section of the reinforcing fibers in the reinforcing fiber orientation direction of the vulcanized rubber sheet was in contact with the sandpaper, and the amount of abrasion after 10 minutes was calculated from the change in weight. The smaller the amount of abrasion, the better the abrasion resistance.

[0042] Example 1 <First step (preparation of aramid nanofiber aqueous dispersion)> 202 g of Twaron (registered trademark) pulp (product number: Type 1094) manufactured by Teijin Aramid Co., Ltd. (solid weight 50 g, moisture weight 152 g), 64 g of additional water, 25 g of potassium hydroxide, and 1,950 g of dimethyl sulfoxide (DMSO) were placed in a 2 L plastic container and mixed at room temperature to prepare a mixed liquid, which was then kept in a dryer set to 70°C for 3 hours.

[0043] After 3 hours at 70°C, the color of the mixture changed from yellow to reddish brown, and no pulp-like material was observed in the mixture. At this point, the mixture was returned to room temperature, and it was visually confirmed that the viscosity had increased compared to immediately after mixing.

[0044] Thereafter, a sufficient amount of water was added to the mixture to coagulate the aramid fiber content derived from Twaron (registered trademark) pulp, and the mixture of DMSO, potassium hydroxide and water was removed while continuing to add water to obtain an agglomerate of the aramid fiber content. The agglomerate was passed through a wet grinder to obtain an aramid nanofiber water dispersion. The obtained aramid nanofiber water dispersion was an aqueous dispersion containing 0.45% by weight of aramid nanofiber.

[0045] <First step (preparation of rubber-water dispersion)> Nipol LX112 (manufactured by Zeon Corporation, containing 40.5% by weight of styrene-butadiene rubber) was diluted 10 times with water to obtain a rubber water dispersion containing 4.05% by weight of styrene-butadiene rubber.

[0046] <First step (preparation of water-containing rubber composition)> The aramid nanofiber water dispersion and the rubber water dispersion were mixed to obtain a mixture in which the weight ratio of the aramid nanofiber to the styrene-butadiene rubber was 10:90 and the weight ratio of the total of the aramid nanofiber and the styrene-butadiene rubber to water was 2.25:97.75.

[0047] This mixture was dried until the weight ratio of the total of the aramid nanofibers and the styrene-butadiene rubber to water became 10:90, to obtain a water-containing rubber composition. The average fiber diameter of the aramid nanofibers in the obtained water-containing rubber composition was 30 nm.

[0048] <Second process> The water-containing rubber composition obtained above was mixed into the unvulcanized rubber compound described below so that the amount of aramid nanofiber mixed was 1% by weight per total weight of the rubber components (natural rubber and styrene-butadiene rubber) contained in the rubber water dispersion and the unvulcanized rubber compound, and the water contained in the rubber mixture was evaporated while kneading for 60 minutes at 140°C in an MS pressure kneader (DS3-10MHHS, manufactured by Moriyama Seisakusho Co., Ltd.), to obtain a solid rubber composition. The obtained solid rubber composition was then left to stand overnight and cooled.

[0049] (Unvulcanized rubber compound composition) Natural rubber: 60 parts by weight Styrene butadiene rubber: 40 parts by weight Coumarone: 10 parts by weight Zinc oxide: 5 parts by weight Stearic acid: 1 part by weight Antioxidant: 1 part by weight Carbon black: 50 parts by weight

[0050] <Third step> Sulfur and N-cyclohexyl-2-benzothiazolyl sulfenamide as a vulcanization accelerator were each added in an amount of 2% by weight per total weight of the rubber components (natural rubber and styrene-butadiene rubber) contained in the solid rubber composition to prepare an unvulcanized rubber composition.

[0051] <Fourth process> The unvulcanized rubber composition was sheeted to a thickness of about 1 mm using an open roll (9-inch test roll manufactured by Kansai Roll Co., Ltd.) to obtain a vulcanized rubber composition sheet. Two vulcanized rubber composition sheets were laminated and press-vulcanized at 150°C for 30 minutes under 1 MPa to obtain a 2 mm thick vulcanized rubber sheet. The components of the water-containing rubber compositions and the physical properties of the vulcanized rubber sheets are shown in Table 1.

[0052] Example 2 In the first step (preparation of a water-containing rubber composition) in Example 1, the mixture was dried until the weight ratio of the total of the aramid nanofibers and the styrene-butadiene rubber to water became 30:70, thereby obtaining a water-containing rubber composition. The average fiber diameter of the aramid nanofibers in the obtained water-containing rubber composition was 30 nm, the same as in Example 1. Using the obtained rubber composition, a vulcanized rubber sheet was produced in the same manner as in Example 1. The evaluation results are summarized in Table 1.

[0053] Example 3 An aramid fiber water dispersion containing 1.01% by weight of aramid nanofibers was prepared in the same manner as in Example 1, except that the amount of water added during preparation of the aramid nanofiber water dispersion was changed. The same rubber water dispersion as in Example 1 was mixed with the above-mentioned aramid nanofiber water dispersion to obtain a mixture in which the weight ratio of the aramid nanofiber to the styrene-butadiene rubber was 20:80 and the weight ratio of the total of the aramid nanofiber and the styrene-butadiene rubber to the water was 2.25:97.75.

[0054] This mixture was dried until the weight ratio of the total of the aramid nanofibers and the styrene-butadiene rubber to water became 10:90, to obtain a water-containing rubber composition. The average fiber diameter of the aramid nanofibers in the obtained water-containing rubber composition was 30 nm. The obtained water-containing rubber composition was used to prepare a vulcanized rubber sheet in the same manner as in Example 1. The evaluation results are shown in Table 1.

[0055] Comparative Example 1 In the first step (preparation of rubber-water dispersion), a water-containing rubber composition with a rubber component to water ratio of 10:90 was obtained using only a latex containing styrene-butadiene rubber (Nipol LX112, active ingredient 40.5 wt%, manufactured by Zeon Corporation) without using aramid nanofibers. The obtained water-containing rubber composition was used to prepare a vulcanized rubber sheet in the same manner as in Example 1. The evaluation results are shown in Table 1.

[0056] Comparative Example 2 In the first step (preparation of an aramid nanofiber aqueous dispersion), aramid nanofibers were not used. Instead, aramid pulp (Twaron (registered trademark) pulp (product number: Type 1094) manufactured by Teijin Aramid Co., Ltd.) was diluted with water to prepare an aqueous dispersion containing 0.45% by weight of aramid pulp, which was used as the aqueous dispersion.

[0057] Other than this, a water-containing rubber composition was obtained in the same manner as in Example 1. The average fiber diameter of the stem portion of the aramid pulp in this water-containing rubber composition was 12 μm (12,000 nm) when observed at 500 times with a scanning electron microscope. The obtained water-containing rubber composition was used to prepare a vulcanized rubber sheet in the same manner as in Example 1. The evaluation results are shown in Table 1.

[0058] Comparative Example 3 A rubber composition was obtained in the same manner as in Example 1, except that the water dispersion containing the aramid nanofibers and the latex of styrene butadiene rubber were mixed, and then the water was completely dried to obtain a water-containing rubber composition in which the ratio of the total amount of the aramid nanofibers and the rubber component to the water equilibrium water content due to water absorption after drying was 99:1.

[0059] The average fiber diameter of the aramid nanofibers in the obtained rubber composition was 30 nm, the same as in Example 1, but it was observed using a scanning electron microscope that the single fibers of the aramid nanofibers having an average fiber diameter of 30 nm were partially aggregated together. The obtained water-containing rubber composition was used to prepare a vulcanized rubber sheet in the same manner as in Example 1. The evaluation results are shown in Table 1.

[0060] [Table 1]

[0061] As shown in Table 1, the vulcanized rubber sheets made from the moisture-containing rubber compositions containing the aramid nanofibers obtained in Examples 1 to 3 exhibited a higher improvement in rubber elasticity modulus and abrasion resistance than the vulcanized rubber sheet made from the moisture-containing rubber composition not containing aramid nanofibers in Comparative Example 1 and the vulcanized rubber sheet made from the moisture-containing rubber composition containing conventional aramid pulp in Comparative Example 2.

[0062] On the other hand, in the vulcanized rubber sheet made from the moisture-containing rubber composition of Comparative Example 3, in which the moisture content of the moisture-containing rubber composition was insufficient and aggregation of the aramid nanofiber single fibers was observed, the effect of improving the rubber elastic modulus and abrasion resistance was smaller than that of the vulcanized rubber sheet made from the moisture-containing rubber composition containing conventional aramid pulp of Comparative Example 2. [Industrial Applicability]

[0063] The water-containing rubber composition of the present invention can be used for tires, transmission belts, rubber hoses, rubber rolls, anti-vibration rubbers, and the like.

Claims

1. A method for producing a rubber molded product, comprising: a first step of mixing an aramid nanofiber water dispersion and a rubber water dispersion in a solids weight ratio of aramid nanofiber to rubber of 1:99 to 35:65, and further removing a part of the water to obtain a water-containing rubber composition (provided that in the water-containing rubber composition, the weight ratio of the total of the aramid nanofibers and the rubber to the water is within a range of 10:90 to 30:70); a second step of mixing the water-containing rubber composition obtained in the first step with a solid rubber, and further removing the water to obtain a solid rubber composition; a third step of mixing the solid rubber composition obtained in the second step with a vulcanizing agent and / or a crosslinking agent to obtain an unvulcanized rubber composition and / or an uncrosslinked rubber composition; and a fourth step of vulcanizing and / or crosslinking the unvulcanized and / or uncrosslinked rubber composition obtained in the third step to obtain a rubber molded product.

2. 2. The method for producing a rubber molded article according to claim 1, wherein the rubber in the rubber-water dispersion is a styrene-butadiene rubber.

Citation Information

Patent Citations

  • Granular elastomer composition and its production

    JP1988137940A

  • Masterbatch of rubber / short fiber, manufacturing method for the same and pneumatic tire using the same

    JP2006206864A

  • Method for manufacturing rubber composition

    JP2011006554A

  • Elastomer composite material and method for manufacturing the same

    JP2011511148A

  • Production method for polymer composition and production method for additive for polymer composition

    JP2013133363A